2011
DOI: 10.1186/1556-276x-6-85
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ge-Sn nanodots on Si(100) surfaces by molecular beam epitaxy

Abstract: The surface morphology of Ge0.96Sn0.04/Si(100) heterostructures grown at temperatures from 250 to 450°C by atomic force microscopy (AFM) and scanning tunnel microscopy (STM) ex situ has been studied. The statistical data for the density of Ge0.96Sn0.04 nanodots (ND) depending on their lateral size have been obtained. Maximum density of ND (6 × 1011 cm-2) with the average lateral size of 7 nm can be obtained at 250°C. Relying on the reflection of high energy electron diffraction, AFM, and STM, it is concluded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
2
4
0
1
Order By: Relevance
“…Then the surfactant-mediated growth has been studied where the surface of the substrate is capped by surfactant layer, altering its physical properties. Various materials were used as a surfactant, such as antimony Sb, bismuth Bi, tin Sn, and some others. For all these systems, a so-called Stranski–Krastanow growth mode is typical.…”
Section: Introductionmentioning
confidence: 99%
“…Then the surfactant-mediated growth has been studied where the surface of the substrate is capped by surfactant layer, altering its physical properties. Various materials were used as a surfactant, such as antimony Sb, bismuth Bi, tin Sn, and some others. For all these systems, a so-called Stranski–Krastanow growth mode is typical.…”
Section: Introductionmentioning
confidence: 99%
“…For GeSn ND epitaxy, it has also been reported that GeSn NDs are formed by low-temperature MBE growth (250 °C-400 °C), and the authors assumed low-temperature growth was made possible by the surfactant effect of Sn. 22) In contrast, because our method for forming GeSn NDs is by annealing amorphous GeSn layers, the mechanism of the low-temperature formation of NDs cannot be explained by only the enhancement of adatoms but should be explained by considering the migration of atoms in the amorphous alloy layers. Because enhancement of migration in amorphous Table II.…”
Section: Discussionmentioning
confidence: 96%
“…14,15) A solution to these problems is to form GeSn QDs under low temperature. 21) Some reports on the formation of GeSn QDs and NDs and theoretical studies have been made in recent years, [22][23][24][25] and electroluminescence (10 K) in the optical communication wavelength range has also been reported. 26) However, further progress is needed to realize light-emitting devices.…”
Section: Introductionmentioning
confidence: 99%
“…There are also a lot of experimental works devoted to the growth of GeSi 2D layers and 3D islands, including the case of the presence of tin, as these systems are very perspective for device applications [24][25][26][27][28][29][30][31][32]. But there is a lack of theoretical investigations capable to predict values of the critical thickness of transition from 2D to 3D growth, mean lateral size, and surface density of quantum dots in the whole range of temperatures, deposition rates, and compositions for these material systems.…”
Section: Introductionmentioning
confidence: 99%